ANALISIS KELAYAKAN USAHA PAVING BLOCK BERBAHAN SAMPAH PLASTIK MENGGUNAKAN BMC DAN PESTLE ANALYSIS - Rekha Rahmania Widiansah; Ansarullah Lawi; I Made Sondra Wijaya; Deni Lorenza (JURNAL REKAYASA SISTEM INDUSTRI, 2026)
Plastic waste is a severe environmental issue in Batam City, where approximately 1,000 tons of waste are generated daily. With 20-30% being plastic and only 17% managed effectively, there is an urgent need for innovative waste reduction solutions. This study conducts a business feasibility analysis of transforming HDPE and LDPE plastic waste into environmentally friendly paving blocks. The research aims to evaluate this sustainable business opportunity utilizing the Business Model Canvas (BMC) to design internal strategies and PESTLE Analysis to assess external macro-environmental factors.The results of the BMC framework reveal a highly viable model targeting environmentally conscious communities, educational institutions, and cafés. The value proposition centers on offering affordable, durable, and eco-friendly construction materials. Key operations involve waste collection, processing, and strategic partnerships with local waste banks and government agencies. Revenue is primarily generated from product sales and collaborative sustainability projects. Concurrently, the PESTLE analysis highlights favorable political support and low economic production costs as significant strengths. Socially, community response is positive, though market awareness requires expansion. Technologically, the production utilizes easily accessible equipment. Legally, obtaining national certification (SNI) is essential for broader market penetration. Environmentally, the business significantly reduces plastic pollution. In conclusion, manufacturing plastic waste-based paving blocks is a highly feasible sustainable business that promotes a circular economy, creates economic value, and mitigates severe local environmental degradation.